Aktivitas antioksidan ekstrak daun katuk (Breynia androgyna L.) dengan metode DPPH serta penetapan kadar fenolat dan flavonoid - Budiana, Wempi; Nuryana, Ela Fitri; Suhardiman, Aris; Kusriani, Herni (Jurnal Agrotek Ummat, 2022)
Concerns about the side effects of synthetic antioxidants consumption have intrigued many researchers to find potential natural antioxidant resources. Most natural antioxidants can be found in plants in the form of phenolic compounds, especially simple phenolics and flavonoids. The aim of this research is to measure antioxidant activity, total phenol and total flavonoid content in katuk leaf extract (Breynia androgyna (L.). The stages of this research are including extraction using several types of solvents, identification of metabolites using thin layer chromatography (TLC), antioxidant activity assay using DPPH, determination of total phenolic content using Folin-Ciocalteu reagent, and determination of total flavonoid content using Chang's method. The results showed that the IC50 values of n-hexane, ethyl acetate, and ethanol extract of katuk leaves from Bandung were 107.52; 67.61; and 39.04 g/mL respectively, whilst for katuk leaves from Sukabumi were 102.39; 67.26; and 27.07 g/mL. Moreover, total phenolic content of n-hexane, ethyl acetate, and ethanol extracts of katuk leaves from Bandung were 12.68; 14.40; and 15.99 mg GAE/g sample respectively, meanwhile for katuk leaves from Sukabumi were 13.14; 14.10; and 16.06 mg GAE/g sample. Furthermore, total flavonoid content for n-hexane, ethyl acetate, and ethanol extract of katuk leaves from Bandung was 6.23; 8.65; and 10.73 mg QE/g sample respectively, while for katuk leaves from Sukabumi it was 6.20; 8.55; and 10.81 mg QE/g sample. In conclusion, the ethanol extract showed the highest antioxidant activity with very strong intensity. Furthermore, simplicia from Sukabumi had higher antioxidant activity than simplicia from Bandung.